The relationship advantage information technologies, sourcing, and management - Kern, Thomas; Willcocks, Leslie (Oxford University Press, 2001)
An insight for both practitioners and academics on how to achieve a relationship advantage, this text examines five case studies, identifying the key dimensions of an outsourcing relationship.